Differences in Action Style Recognition in Children with Autism Spectrum Disorders - Di Cesare, Giuseppe; Sparaci, Laura; Pelosi, Annalisa; Mazzone, Luigi; Giovagnoli, Giulia; Menghini, Deny; Ruffaldi, Emanuele; Vicari, Stefano (Frontiers in Psychology, 2017)
Vitality form is a term, originally introduced by Stern (2010), to describe “how” an action is performed. The capacity to perceive the vitality form of others’ actions is a fundamental element of social interactions and a basic way of relating to and understanding others’ behaviors. Although vitality forms characterize all human interactions, few studies have addressed their role in social and communicative disorders such as autism. The aim of the present study is to evaluate the ability to recognize different vitality forms during the observation of different motor actions in a group of children with autism spectrum disorders (ASD) compared to typically developing controls (TD). Results show a significant difference between children with ASD and TD in vitality forms recognition. This finding sheds new light on how children with ASD understand others’ actions providing new ideas on overall social understanding as well as useful insights for professionals and caregivers alike.